2010
DOI: 10.1016/s0034-7094(10)70045-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acute Normovolemic Hemodilution on Blood Coagulation: Comparison between Tests of an In Vivo and an In Vitro Model

Abstract: Souza MAB, Klamt JG, Garcia LV-Effects of Acute Normovolemic Hemodilution on Blood Coagulation: Comparison between Tests of an In Vivo and an In Vivo Models. Background and objectives: Normovolemic hemodilution produces conflicting results on hemostasis, since works differ according to the fluids used, degree of hemodilution, method used to evaluate hemostasis, and the way used to produce hemodilution. The effects of hemodilution on hemostasis can depend on how it is done and whether an in vivo or an in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…While increased PT time is a nonspecific marker, the decreased fibrinogen levels and increased PT times observed in the study are consistent with dilutional coagulopathy as well . De Souza et al associated decreases in fibrinogen levels and platelet counts and increases in PT and PTT times in vivo and in vitro with hemodilution using lactated ringers solution . Fibrinogen depletion is also known to be the first factor to reach critically low levels during dilutional coagulopathy, and was found to be associated with transfusions in this cohort .…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…While increased PT time is a nonspecific marker, the decreased fibrinogen levels and increased PT times observed in the study are consistent with dilutional coagulopathy as well . De Souza et al associated decreases in fibrinogen levels and platelet counts and increases in PT and PTT times in vivo and in vitro with hemodilution using lactated ringers solution . Fibrinogen depletion is also known to be the first factor to reach critically low levels during dilutional coagulopathy, and was found to be associated with transfusions in this cohort .…”
Section: Discussionmentioning
confidence: 53%
“…25 De Souza et al associated decreases in fibrinogen levels and platelet counts and increases in PT and PTT times in vivo and in vitro with hemodilution using lactated ringers solution. 28 Fibrinogen depletion is also known to be the first factor to reach critically low levels during dilutional coagulopathy, and was found to be associated with transfusions in this cohort. 37 Lastly, dilutional coagulopathy during major orthopedic surgery was previously shown to be principally a problem of fibrinogen polymerization.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“… reported that 50% haemodilution with crystalloid caused a hypocoagulable state. Although viscoelastometric analysis was not used to assess the coagulation state, the coagulation parameters were prolonged in vitro after ANH with crystalloid, indicating a hypocoagulable state . In our study, each patient lost 960 ml autologous blood .…”
mentioning
confidence: 77%